Calibration of foundation movements for AASHTO LRFD bridge design specifications. Issue 3 (3rd July 2019) - Samtani, Naresh C.; Kulicki, John M.
ABSTRACT: In the bridge design specifications of the American Association of State Highway and Transportation Officials using the Load and Resistance Factor Design method, the loads and resulting force effects are given two-letter designations, e.g. " SE " for "force effects due to settlement". The same two-letter designation is used as a subscript to distinguish load factors, γ, to be applied to loads and other actions acting on the bridge. Thus, the load factor γ SE is used to develop factored values of the additional induced force effects such as moments and shears in a bridge structure due to foundation movements. This paper presents the process to calibrate the SE load factor as a function of the target reliability index based on structural service limit states such as cracking in a bridge superstructure. In this process, the target reliability index, uncertainty in predicted movements, and user-specified deterministic tolerable movements are considered in a unified manner. The calibration process can be used for any analytical method and any pattern of movement. The calibration process is demonstrated by an example of immediate settlement for five analytical methods using a dataset based on 20 instrumented spread footings from 10 bridges in the northeast USA.